Forward Body Biased Low Power 4.0-10.6 GHz Wideband Low Noise Amplifier - Rohit Goel; Anil Kumar; Mahesh Kumar; Sandeep Kumar (IAES Indonesian Section, 2022)
A forward body biased low power Low Noise Amplifier (LNA) is designed using Common Gate (CG) topology. By using current reuse technique between the first stage and second stage Common Source topology accompanied with forward body biasing leads to low power dissipation. A series to parallel tank circuit at this stage leads to wideband design. A shunt peaking inductor at the drain terminal of second stage causes the higher frequency peak to increase leading to wide bandwidth. Two CS cascade stages are used to increase the overall gain of the proposed LNA with a buffer stage at the output for output matching. The proposed LNA attained maximum gain of 26.39 dB with a gain greater than 16 dB over entire range. The circuit gives reflection coefficient less than – 10 dB with NF 2.7 dB. With Vdd of 0.925 V, a DC current of 8.32 mA is consumed giving 7.7 mW power consumption.